Competing Effects of Chlorination on the Strength of Te⋅⋅⋅O Chalcogen Bonds Select the Structure of Mixed Supramolecular Macrocyclic Aggregates of Iso‐Tellurazole N‐Oxides. Issue 42 (9th June 2021) - Ho, Peter C.; Lomax, Justin; Tomassetti, Valerie; Britten, James F.; Vargas‐Baca, Ignacio
Abstract: Chlorination of 3‐methyl‐5‐phenyl‐1, 2‐tellurazole‐2‐oxide yielded the λ 4 Te dichloro derivative. Its crystal structure demonstrates that the heterocycle retains its ability to autoassociate by chalcogen bonding (ChB) forming macrocyclic tetramers. The corresponding Te⋅⋅⋅O ChB distances are 2.062 Å, the shortest observed to date in aggregates of this type. DFT−D3 calculations indicate that while the halogenated molecule is stronger as a ChB donor it also is a weaker ChB acceptor; the overall effect is that the ChBs in the chlorinated homotetramer are not significantly stronger. However, partial halogenation or scrambling selectively yield the 2 : 2 heterotetramer with alternating λ 4 Te and λ 2 Te centers, which calculations identified as the thermodynamically preferred arrangement. Abstract : Chlorination of tellurium has opposing effects on the formation of chalcogen bonds (ChBs) by iso‐tellurazole N ‐oxides, enhancing their strength as ChB donors but weakening their role as ChB acceptors. The net effect is that the fully chlorinated tetramer is barely more stable than the non‐halogenated macrocycle. In contrast, partial halogenation results in a more stable alternating structure.